(untitled) (Journal of the College of Basic Education, 2022)
The detection of cytokines in the urine and serum have been used in the diagnosis and monitoring of various urological disease. In this study Interleukine – 6 (IL-6) level in serum and urine have been measured in acute pyelonephritis ( APN) in children patients . A total of ( 95) urine &blood sample have been collacted from children ( 2 month – 12 years) suffering from fever, dysurea,frequency. Twenty –sex patient of APN were include in the present study as well as twenty children of the same age range as control group. Acute pyelonephritis is suggested by flank pain ,nausea and vomiting, those patients have been diagnosed by the physician and the diagnosis is confirmed by available investigation methods ,laboratory test , ultrasound . White blood cells (WBCs)& nutrophile count as well as C-reactive protein (CRP) were high significant in APN patients while blood urea &serum creatinine levels were non significant in comparision with control group. High significant differences were noticed between the sex groups of APN patients (P- value ≤0.01),percentage of male patients was (65.38) larger than that of females (34.62). Also important differences have been found between APN patients in the age groups ; percentage of disease is the lowest in the age range ( 1-2) years ,and highest in the age range ( more than 2 years). Urine & Serum IL-6 concentrations were significantly high with means ;109.24 ,28.86 pg/ml respectively compared with control means (12.59,7.93 pg/ml) at (P- value ≤ 0.05).